Spectrophotometric evaluation of restorative composite shades and their match with a classical shade guide - Rafael Melara; Luciana Mendonça; Fábio Herrmann Coelho-de-Souza; Juliana Nunes Rolla; Luciano de Souza Gonçalves (Restorative Dentistry & Endodontics, 2021)
ObjectivesThe aim of this study was to verify the match between 5 shades of composites from different manufacturers with a shade guide and among the systems using a portable spectrophotometer.Materials and MethodsShade measurements were performed on specimens of Z350 XT (3M ESPE), Charisma Diamond (Heraeus Kulzer GmbH), Esthet X-HD (Dentsply Caulk), and Empress Direct (Ivoclar-Vivadent) for shades A1, A2, A3, B1, and C3 using a Vita Easyshade spectrophotometer (Vita Zahnfabrik) against a white background. Corresponding shades of Vitapan Classical (Vita Zahnfabrik) guide were measured likewise and shade variation (ΔE) was calculated based on International Commission on Illumination L*a*b* parameters. The ΔE of the composites in each shade was compared by one-way analysis of variance and Tukey's post hoc test (α = 0.05).ResultsAll composites presented ΔE > 3.7 compared with the shade guide. Variation in shades A3, B1, and C3 was significantly different for all composites. ΔE of Z350 XT was significantly lower for A1 than for the other shades, whereas ΔE of Z350 XT and Charisma Diamond were significantly lower for A2 than for the other shades.ConclusionsNo composite shade matched with the shade guide. Equivalent shades of the restorative composite from different manufacturers may show clinically noticeable ΔE.